A universal strategy for preparing carbon quantum dot-based composites with blue and green afterglow luminescence. (18th October 2021) - Zhu, Yaqing; Bai, Jianliang; Huang, Zhujun; Yuan, Guojun; Zhang, Lu; Wang, Xinyu; Ren, Lili
Abstract : Afterglow materials, such as room temperature phosphorescence (RTP) or delayed fluorescence (DF) materials, have been paid lots of attention due to their unique optical properties and great potential applications. Abstract : Afterglow materials, such as room temperature phosphorescence (RTP) or delayed fluorescence (DF) materials, have been paid lots of attention due to their unique optical properties and great potential applications. However, most afterglow materials currently studied such as metal-containing composite luminescent materials have certain biological toxicity. Carbon quantum dots (CQDs), with excellent optoelectronic and tunable optical properties have become a kind of environmentally-friendly nano luminescent material because of their low toxicity and good biocompatibility. Recently, the afterglow properties of CQDs have attracted significant interest. Nevertheless, afterglow CQDs still face challenges such as color-tunable afterglow and easy quenching in aqueous environments. Here, we have proposed a universal strategy for dispersing CQDs into cyanuric acid (CA) to prepare CQDs–CA composites, which simultaneously exhibit dark-blue DF and blue RTP (after 254 nm excitation), and green RTP (after 365 nm excitation). The afterglow lifetimes exceed 1 s. Even in extreme conditions (pH = 1 or 14), the afterglow in the aqueous solution still persists. The excellent afterglow properties and good stability make CQDs–CA a promising material for fingerprinting and advanced anti-counterfeiting applications.